Manipulating the mitochondria activity in human hepatic cell line Huh7 by low-power laser irradiation - Lynnyk, Anna; Lunova, Mariia; Jirsa, Milan; Egorova, Daria; Kulikov, Andrei; Kubinová, Šárka; Lunov, Oleg; Dejneka, Alexandr (Biomedical optics express, 2018)
Low-power laser irradiation of red light has been recognized as a promising tool across a vast variety of biomedical applications. However, deep understanding of the molecular mechanisms behind laser-induced cellular effects remains a significant challenge. Here, we investigated mechanisms involved in the death process in human hepatic cell line Huh7 at a laser irradiation. We decoupled distinct cell death pathways targeted by laser irradiations of different powers. Our data demonstrate that high dose laser irradiation exhibited the highest levels of total reactive oxygen species production, leading to cyclophilin D-related necrosis via the mitochondrial permeability transition. On the contrary, low dose laser irradiation resulted in the nuclear accumulation of superoxide and apoptosis execution. Our findings offer a novel insight into laser-induced cellular responses, and reveal distinct cell death pathways triggered by laser irradiation. The observed link between mitochondria depolarization and triggering ROS could be a fundamental phenomenon in laser-induced cellular responses.
Keywords: (170.1420) Biology; (170.0170) Medical optics and biotechnology; (170.1530) Cell analysis